Varieties of violence in street culture - Tutenges, Sébastien (Deviant behavior, 2024)
Violence is central to social life, especially for people at the margins of urban society. This article examines ethnographic data collected in Oslo among individuals who are involved in street life and crime. We propose the following typology for understanding violence in this population: respect-based violence, business violence, drunken violence, and family violence. We argue that from an emic perspective, these types are substantially different from one another and evoke varying moral evaluations. Violence that has to do with respect, business, or drinking tends to be tolerated, sometimes even celebrated, whereas family violence tends to be condemned. Violence is not a uniform phenomenon. It comes in different types and is experienced and made sense of differently across cultural contexts. These findings challenge a dominating trend in contemporary micro-sociology, spearheaded by Randall Collins, which focuses on identifying universal rules of violent situations at the expense of sensitivity to cultural variation.